Upper body structure design for solar car - Muhammad Syafiq, Ayob (2010)
This report presents on the design of upper body structure for solar car. Solar car uses solar energy from the sun to convert it into electrical energy in order to move the solar car. In order to move the solar car smoothly, the shape of solar car’s body must be more aerodynamics to get low drag and reduce the friction at the same time. The objective of this report is to propose several design of solar car’s body and analyze the models for drag coefficient and justify the most aerodynamics model. The report describes the aerodynamics concept use in common cars, computational fluid dynamics (CFD) analysis to calculate the drag coefficient and identify material and dimension of solar car. The dimension for the project is guided by World Solar Challenge regulations 2009 technical specifications. Fibreglass, kevlar and carbon fiber materials were studied in this report which is commonly used in nowadays solar car. The models of solar car were designed by using the computer-aided drawing software which is Solid Work. The CFD analysis was then performed using COSMOSFloWorks. Each model of solar car was analyzed using different mesh and speed of the air flow. Finally, the drag force of each model is obtained and used in the calculation to find coefficient of drag for each model. From the result, it is observed that frontal area and shape of the solar car’s body are the most important parameter to be considered in order to design an aerodynamics car. Besides designing the aerodynamics shape of solar car, the choice of material for body can also affect the performance of the vehicle because different material will contribute the weight of the vehicle. As the vehicle is lighter, it will improve the vehicle power to weight ratio. Thus, improve the performance of the vehicle.